2016
DOI: 10.4049/jimmunol.1502203
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Inflammasome Activation Characterizes Tuberculosis-Associated Immune Reconstitution Inflammatory Syndrome

Abstract: Tuberculosis-associated immune reconstitution inflammatory syndrome (TB-IRIS) complicates combination antiretroviral therapy (cART) in up to 25% of patients with HIV/TB coinfection. Monocytes and IL-18, a signature cytokine of inflammasome activation, are implicated in TB-IRIS pathogenesis. In this study, we investigated inflammasome activation both pre- and post-cART in TB-IRIS patients. HIV/TB patients exhibited higher proportions of monocytes expressing activated caspase-1 (casp1) pre-cART, compared with HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 65 publications
6
47
2
Order By: Relevance
“…Similar to earlier time points, neutrophil-dependent inflammatory responses (MMP9, CTSG, and LCN2) continued to be transcriptionally up-regulated ( Table S3 ) in patients with TBM-IRIS. Inflammasome activation has recently been shown as an important mediator of tuberculosis-IRIS in 2 independent studies [9, 11]. In accordance with these results, functional analysis of the differentially abundant transcript also indicated significant up-regulation of transcripts associated with inflammasome activation (Figure 3B).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Similar to earlier time points, neutrophil-dependent inflammatory responses (MMP9, CTSG, and LCN2) continued to be transcriptionally up-regulated ( Table S3 ) in patients with TBM-IRIS. Inflammasome activation has recently been shown as an important mediator of tuberculosis-IRIS in 2 independent studies [9, 11]. In accordance with these results, functional analysis of the differentially abundant transcript also indicated significant up-regulation of transcripts associated with inflammasome activation (Figure 3B).…”
Section: Resultssupporting
confidence: 83%
“…We have previously shown that Toll-like receptor signaling and inflammasome activation are key mediators of dysregulated cytokine production in a cohort of patients with heterogenous presentations of paradoxical tuberculosis-IRIS [9]. Most recently, Tan and colleagues [11] have also reported that monocytes from patients with tuberculosis-IRIS displayed aberrant inflammasome activation and had greater cell death both before and after ART. …”
Section: Discussionmentioning
confidence: 99%
“…Although initiation of ART during treatment of TBM is associated with a reduced 6 mo mortality (HR 0.3, 95% CI = 0.08–0.82) IRIS in this context carries a poor prognosis with one study reporting a mortality rate of 25% with severe disability at 9 mo observed in 23% of those who survived . The role of inflammasomes, immune complexes of receptors, and sensors that mediate innate immune responses and lead to inflammation, have been described in this setting …”
Section: Differences In the Intracerebral Immune Response In The Hiv‐mentioning
confidence: 99%
“…A higher frequency of HBsAg loss has been associated with lower CD4+ T cell count prior to initiation of HBV-active ART [114, 115, 117] and a greater increase in CD4+ T-cells following ART [115, 118] but many of these studies were retrospective or didn’t include individuals with low CD4+ T-cells prior to ART. The relationship between low CD4+ T-cell count and enhanced HBsAg loss and seroconversion may potentially be secondary to brisk immune reconstitution that has been associated with high levels of IL18 production which could enhance dendritic cell function, adaptive immunity and antibody production [119] .…”
Section: Natural History Of Hiv-hbv Co-infection In the Era Of Hbvmentioning
confidence: 99%